The Effectiveness of Learning Videos as a Source of Digital Literacy on Poster Learning in Elementary Schools - Maulid, Maulana Nur; Sakti, Asri Wibawa (Indonesian Journal of Multidiciplinary Research, 2022)
Learning in elementary schools tends to focus on teachers so it is less empowering for students. Of course, this makes the low level of literacy process in student learning the purpose of this study is to find out the effectiveness of the use of video media as digital literacy on poster learning in elementary school. This study uses quantitative research methods using the pre-experimental method of design type one group pre-test and post-test. The subjects in the study were 10 grade III elementary school students consisting of 5 male students and 5 female students. The results of the study showed that the knowledge of students and students about poster material before and after the implementation of video media as digital literacy is remembered. Because learning videos are very helpful to students in understanding poster material. It can be concluded that the delivery of material through this video can indirectly improve digital literacy for students.